The mycorrhizal tragedy of the commons. (22nd March 2021) - Henriksson, Nils; Franklin, Oskar; Tarvainen, Lasse; Marshall, John; Lundberg‐Felten, Judith; Eilertsen, Lill; Näsholm, Torgny
Abstract: Trees receive growth‐limiting nitrogen from their ectomycorrhizal symbionts, but supplying the fungi with carbon can also cause nitrogen immobilization, which hampers tree growth. We present results from field and greenhouse experiments combined with mathematical modelling, showing that these are not conflicting outcomes. Mycorrhizal networks connect multiple trees, and we modulated C provision by strangling subsets of Pinus sylvestris trees, assuming that carbon supply to fungi was reduced proportionally to the strangled fraction. We conclude that trees gain additional nitrogen at the expense of their neighbours by supplying more carbon to the fungi. But this additional carbon supply aggravates nitrogen limitation via immobilization of the shared fungal biomass. We illustrate the evolutionary underpinnings of this situation by drawing on the analogous tragedy of the commons, where the shared mycorrhizal network is the commons, and explain how rising atmospheric CO2 may lead to greater nitrogen immobilization in the future. Abstract : Trees receive growth‐limiting nitrogen from their ectomycorrhizal symbionts, but supplying the fungi with C can also cause nitrogen immobilization, which hampers tree growth. We present a model based on measurements from greenhouse and field studies, indicating that these are not contradictory outcomes. Trees connected via common mycorrhizal networks seek to maximize their individual competitiveness, which can lead to over‐investment in ectomycorrhiza, aggravating overall nitrogen immobilization in fungal biomass.